TINGKAT PENGETAHUAN IBU HAMIL TENTANG TANDA-TANDA BAHAYA KEHAMILAN DI DESA GEMULAK KECAMATAN SAYUNG KABUPATEN DEMAK - Susiloningtyas, Is (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The success of maternal health efforts, can be seen from indicator of maternal mortality rate. Based on Indonesia Demographic and Health Survey I) in 2012, MMR associated with pregnancy, childbirth and postpartum is 359 per 100,000 live births. The main causes of death are bleeding, hypertension in pregnancy and infection. Efforts to decrease MMR with ANC regularly. The purpose of this research is to know the description of pregnant woman’s knowledge level about signs of risk pregnancy in village Gemulak of Demak Sayung distrit. The method of research used descriptive using cross sectional approach. Research used design by doing measurement or observation or time. The population were pregnant women in the village Gemulak 32 pregnant women. The research instrument used questionnaire. The results of the study of 32 pregnant women, mothers aged 20-35 years are 20 people (62,50) %, aged less than 20 years are 7 people (21.86%), and these age over 35 years are 5 people (15.63%). Mothers with junior high school education are 10 respondents (31.25%), primary school education are 9 respondents (28.13%), senior high school education are 7 respondents (21.88%), did not graduate Primary Schools are 5 respondents (15.63%), and these with college education is 1 respondent (3.13%). Pregnant women with moderate level of knowledge are 14 respondents (43.75%), 10 respondents (31.25%) had less knowledge level, and 8 respondents (25%) had a good level of knowledge about the signs of pregnancy hazard. Conclusion Majority of respondents have moderate knowledge about pregnancy alert that are 14 responden (43,75%). Keywords: Knowledge, signs of risk pregnancy